The role of blood groups in the development of diabetes mellitus after gestational diabetes mellitus - Karagoz H; Erden A; Ozer O; Esmeray K; Cetinkaya A; Avci D; Karahan S; Basak M; Bulut K; Mutlu H; Simsek Y (Dove Medical Press, 2015)
Hatice Karagoz,1 Abdulsamet Erden,2 Ozerhan Ozer,2 Kubra Esmeray,2 Ali Cetinkaya,2 Deniz Avci,2 Samet Karahan,2 Mustafa Basak,2 Kadir Bulut,2 Hasan Mutlu,3 Yasin Simsek4 1Internal Medicine Department, Acibadem Kayseri Hospital, 2Internal Medicine Department, 3Medical Oncology Department, 4Endocrinology Department, Kayseri Training and Research Hospital, Kayseri, Turkey Introduction: Gestational diabetes mellitus (GDM) is a common condition that is defined as glucose intolerance of varying degree with onset or first recognition during pregnancy and it affects approximately 5% of all pregnancies all over the world. GDM is not only associated with adverse pregnancy outcomes such as macrosomia, dystocia, birth trauma, and metabolic complications in newborns, but it is also a strong predictor of transitioning to overt DM postpartum. The association of ABO blood groups with DM has been observed before in several epidemiological and genetic studies and resulted with inconsistent findings, but still there are not enough studies in the literature about the association of ABO blood groups with GDM. In this study, we aimed at investigating any possible relationship between the ABO blood group system and GDM and also the transitioning of GDM to overt DM postpartum, in Turkey.Patients and methods: A total of 233 patients with GDM from Kayseri Training and Research Hospital between 2002 and 2012 were included in the study. The cases that have serologically determined blood groups and Rh factor in the hospital records were included in the study, and the patients with unknown blood groups were excluded. Patients were classified according to blood groups (A, B, AB, and O) and Rh status (+/-). GDM was diagnosed based on the glucose cut-points of the International Association of the Diabetes and Pregnancy Society Groups. The distributions of blood groups of the patients with GDM were compared with the distribution of blood groups of 17,314 healthy donors who were admitted to the Turkish Red Crescent Blood Service in our city in 2012.Results: There was a significant difference between the patients with GDM and control group in terms of distribution of ABO blood groups. Blood group AB was found to be higher in the patients with GDM compared to the control group (P=0.029). When the patients were compared according to the development of DM, the ratio of group O was higher than others, while the ratio of group B was lower in the group developing DM (P=0.001). There was a significant difference between the groups – GDM patients with or without DM – in terms of distribution of ABO blood groups with Rh factor and the ratio of developing DM is found to be higher in patients with +Rh factor among all the blood groups except for group B (P=0.008). Conclusion: In this study, we found a higher risk of GDM for the patients with blood group AB, which means that we have to be more careful on the follow-up of pregnant women with blood group AB. The patients with GDM of blood group O are under a higher risk of developing DM and also +Rh factor must be considered as another risk factor, so these patients should be closely followed postpartum by the oral glucose tolerance tests. To our knowledge, this is the first analysis that investigates the association between the ABO blood groups and transitioning to DM after GDM. Keywords: gestational diabetes mellitus, ABO blood groups, Rh factor